Intravenous immunoglobulins as first-line treatment in idiopathic inflammatory myopathies: a pilot study. (25th October 2020) - Lim, Johan; Eftimov, Filip; Verhamme, Camiel; Brusse, Esther; Hoogendijk, Jessica E; Saris, Christiaan G J; Raaphorst, Joost; De Haan, Rob J; van Schaik, Ivo N; Aronica, Eleonora; de Visser, Marianne; van der Kooi, Anneke J
Abstract: Objectives: We explored efficacy and safety of IVIg as first-line treatment in patients with an idiopathic inflammatory myopathy. Methods: In this investigator-initiated phase 2 open-label study, we included 20 adults with a newly diagnosed, biopsy-proven idiopathic inflammatory myopathy, and a disease duration of less than 9 months. Patients with IBM and prior use of immunosuppressants were excluded. The standard treatment regimen consisted of IVIg (Privigen) monotherapy for 9 weeks: a loading dose (2 g/kg body weight) and two subsequent maintenance doses (1 g/kg body weight) with a 3-week interval. The primary outcome was the number of patients with at least moderate improvement on the 2016 ACR/EULAR Total Improvement Score. Secondary outcomes included time to improvement, the number of patients requiring rescue medication and serious adverse events. Results: We included patients with DM ( n = 9), immune-mediated necrotizing myopathy ( n = 6), non-specific myositis/overlap myositis ( n = 4) and anti-synthetase syndrome ( n = 1). One patient was excluded from analyses because of minimal weakness resulting in a ceiling effect. Eight patients (8/19 = 42.0%; Clopper–Pearson 95% CI: 19.6, 64.6) had at least moderate improvement by 9 weeks. Of these, six reached improvement by 3 weeks. Seven patients required rescue medication due to insufficient efficacy and prematurely ended the study. Three serious adverse events occurred, of which one was pulmonary embolism. Conclusion: First-line IVIg monotherapy led to at least moderate improvement in nearly half of patients with a fast clinical response in the majority of responders. Trial registration: Netherlands Trial Register identifier, NTR6160.